Evaluation of the Level of Financial Inclusion among Businesses from the Next 11 Group of Countries - Puszer, Blandyna; Cichorska, Joanna (Journal of Finance and Financial Law, 2021)
The purpose of the article. The article aims to evaluation which factors are a barrier to financial inclusion in the Next 11 countries. The research aim of this article is to assess the differences in the degree of financial inclusion of business entities from the Next 11 group of countries by taking into consideration the use of basic banking services such as bank accounts, credit lines and loans.The hypothesis of the article. The authors put forward the hypothesis that in poorly developed countries, to which the Next 11 countries belong, there are considerable areas of financial exclusion among businesses, in particular among small and medium-sized enterprises. In most of these countries, corporate financial inclusion rates are below the global average.Methodology. The article applies the following research methods: a critical analysis of the literature in the theoretical part; and desk research analysis (that is analysis of data gathered) in the empirical part. Research into the degree of financial inclusion in Next 11 countries was conducted on the basis of indicators of the use of banking services by enterprises operating in Next 11 countries.Results of the research. The level of companies’ financial inclusion depends above all on the degree to which they make use of bank accounts and bank loans. Countries in different geographical locations vary in terms of economic and technological development and social awareness, which impacts on their participation in the use of banking services.Analysis of the basic indicators of banking services availability showed that there is a widespread problem of financial exclusion for companies in Next 11 countries. The proportion of companies possessing a current bank account was below the average of all countries worldwide. However, the worst situation exists in the field of financing business activity using foreign capital. Credit lines there are used on average by less than 25% of companies. However, Next 11 group countries do not see the lack of available credit lines as the main barrier to development.